2011
DOI: 10.1073/pnas.1107519108
|View full text |Cite
|
Sign up to set email alerts
|

Pigeons steer like helicopters and generate down- and upstroke lift during low speed turns

Abstract: Turning is crucial for animals, particularly during predator-prey interactions and to avoid obstacles. For flying animals, turning consists of changes in (i) flight trajectory, or path of travel, and (ii) body orientation, or 3D angular position. Changes in flight trajectory can only be achieved by modulating aerodynamic forces relative to gravity. How birds coordinate aerodynamic force production relative to changes in body orientation during turns is key to understanding the control strategies used in avian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
98
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(106 citation statements)
references
References 42 publications
6
98
2
Order By: Relevance
“…In sum, these wing motions and the resulting induction of velocity into the air would likely be beneficial to a bird seeking to move forward. This observation is corroborated by our A B 25% 35% 45% 55% 65% 10% 30% 40% 50% previous model of the tip-reversal upstroke (Crandell and Tobalske, 2011) and kinematic measurements of whole-body acceleration that are consistent with an aerodynamically active upstroke in pigeons, a species that uses tip-reversal (Ros et al, 2011). Recent measurements in parrotlets (Forpus coelestis), a species that exhibits tip-reversal in slow flight, indicates minimal weight support; thrust was not measured (Lentink et al, 2015).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In sum, these wing motions and the resulting induction of velocity into the air would likely be beneficial to a bird seeking to move forward. This observation is corroborated by our A B 25% 35% 45% 55% 65% 10% 30% 40% 50% previous model of the tip-reversal upstroke (Crandell and Tobalske, 2011) and kinematic measurements of whole-body acceleration that are consistent with an aerodynamically active upstroke in pigeons, a species that uses tip-reversal (Ros et al, 2011). Recent measurements in parrotlets (Forpus coelestis), a species that exhibits tip-reversal in slow flight, indicates minimal weight support; thrust was not measured (Lentink et al, 2015).…”
Section: Discussionsupporting
confidence: 72%
“…In vivo accelerometers mounted to the trunk of a cockatiel (Nymphicus hollandicus) also indicate that the tipreversal upstroke produces 14% of the net force of downstroke (Hedrick et al, 2004). Lastly, kinematic analyses of pigeons suggest the upstroke produces 50% of the net force of the downstroke during slow-speed maneuvering (Ros et al, 2011). However, the aerodynamic mechanism remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The wings started to unfold at the same moment as the acceleration profiles of ground reaction forces and kinematics start to diverge (Fig.2A,C). We suggest that forces produced by the wings (Crandell and Tobalske, 2011;Ros et al, 2011) may be responsible for a part of the observed disparity between ground reaction forces and observed kinematics in diamond dove. However, it seems unlikely that zebra finch is generating an aerodynamically active upstroke, as the species uses a flexed-wing upstroke (Tobalske et al, 1999), and no aerodynamic activity was visible in the wake.…”
Section: Discussionmentioning
confidence: 98%
“…Diamond doves use a tip-reversal upstroke, and we hypothesize that this style of upstroke is aerodynamically active (Crandell and Tobalske, 2011;Ros et al, 2011). Tip-reversal may provide an earlier onset of useful aerodynamic force production during the first wingbeat in diamond dove.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation